2023
DOI: 10.3390/app13179533
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Ion Bombardment Induced Heat Flux on the Wafer Surface in Inductively Coupled Plasma Reactive Ion Etch

Sung Il Cho,
Hyun Keun Park,
Surin An
et al.

Abstract: Plasma plays an important role in semiconductor processes. With the recent miniaturization and integration, the control of plasma became essential for success in the critical dimension of a few nanometers and etch narrow and deep holes with their high aspect ratios. Recently, the etching process has reached physical limitations due to a significant increase in wafer surface temperature under the elevated amount of RF power, affecting not only the warpage phenomenon, but also etching uniformity and etching prof… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…It has been reported that having high porosity with narrow pore-to-pore spacing (i.e., S smaller than half of the cell diameter) is critical in improving the sample processing The transition of the photoresist shape is consistent with the surface tension caused shape change after photoresist melting [29,30]. It is also well known that the ion bombardment of the RIE process can heat the sample surface [31,32]. Therefore, we hypothesize that ion bombardment from the Vertical Sidewall RIE recipe have high enough energy to melt the photoresist mask that causes vertical sidewalls in parylene pores.…”
Section: Dependance Of Maximum Thickness Of Porous Parylene Membrane ...mentioning
confidence: 77%
“…It has been reported that having high porosity with narrow pore-to-pore spacing (i.e., S smaller than half of the cell diameter) is critical in improving the sample processing The transition of the photoresist shape is consistent with the surface tension caused shape change after photoresist melting [29,30]. It is also well known that the ion bombardment of the RIE process can heat the sample surface [31,32]. Therefore, we hypothesize that ion bombardment from the Vertical Sidewall RIE recipe have high enough energy to melt the photoresist mask that causes vertical sidewalls in parylene pores.…”
Section: Dependance Of Maximum Thickness Of Porous Parylene Membrane ...mentioning
confidence: 77%
“…Conventional holding and cooling the wafer-temperature from the wafer backside on ESC should also include the additional heating amount appears on the front side of the wafer from the increased ion bombardment of the plasma. [8][9][10] Wafer-temperature control by heat source has received considerable attention, and several coolant modeling has been patented. 11,12) Nevertheless, only a few scientific papers have been published on the design of backside gas flows that interact most closely with a wafer.…”
Section: Introductionmentioning
confidence: 99%